THE LONGITUDINAL FORCES ARISING IN A WAY BEFORE THE BRAKING TRAIN - Matvietsov, V. I.; Kovtun, P. V.; Kiebikov, O. O. (Science and Transport Progress, 2003)
The results of experiment on definition of the additional longitudinal forces arising in a railway ahead of a braking train are considered in the article.